Making Data Flow for the Climate Risk Market. (December 2017) - Bates, Jo; Goodale, Paula
In 2011, the U.K. government announced that the national meteorological agency would be releasing a significant volume of data as part of its Open Data policy agenda. This article explores the interrelationship between this announcement and efforts to boost the competitiveness of the United Kingdom's weather derivatives industry. Primary qualitative data are analyzed to produce a genealogical account of these policy developments, and Braman's concept of "informational power" is used to frame a critical narrative of the broader dynamics of power at play. We argue that although there have been significant tensions around efforts to open the United Kingdom's weather data, these have largely been absorbed by and, ultimately, contained within the hegemonic structures of the United Kingdom's neoliberal state. We conclude by arguing that this struggle needs to be broadened and externalized beyond the state so that critical questions about the deepening data-driven financialization of climate change can be addressed.